Compositional magnetic resonance imaging in the evaluation of the intervertebral disc: Axial vs sagittal T2 mapping. Issue 9 (5th June 2020) - Raudner, Marcus; Schreiner, Markus M.; Weber, Michael; Juras, Vladimir; Stelzeneder, David; Windhager, Reinhard; Trattnig, Siegfried
Abstract: The aim of this study was to assess T2 values of the lumbar intervertebral discs in the axial and sagittal plane views and assess their respective interobserver reliability. The lumbar intervertebral discs of 23 symptomatic patients (11 female; 12 male; mean age, 44.1 ± 10.6; range, 24‐64 years) were examined at 3T. Region‐of‐interest (ROI) analysis was performed on axial and sagittal T2 maps by two independent observers. Intraclass correlation coefficient (ICC) was assessed for every ROI. The interobserver agreement was excellent for the nucleus pulposus (NP) in the sagittal (0.951; 95% confidence interval [CI], 0.926‐0.968) and axial (0.921; 95% CI, 0.845‐0.955) planes. The posterior 20% region showed a higher ICC in the axial vs the sagittal assessment (0.845; 95% CI, 0.704‐0.911 vs 0.819; 95% CI, 0.744‐0.873). The same was true for the posterior 10%, with the axial ROI showing a higher ICC (0.923; 95% CI, 0.865‐0.953 vs 0.628; 95% CI, 0.495‐0.732). The intraobserver agreement was excellent for every ROI except the sagittal 10% region, which showed good performance (0.869; 95% CI, 0.813‐0.909). The sagittal nucleus pulposus was the best‐performing ROI with regard to intra‐ and interobserver agreement in the T2 assessment of the lumbar intervertebral disc. However, the axial NP showed more stable agreements overall and across the value range. In addition, the annular analysis showed better inter‐ and intraobserver agreement in the axial plane view. Clinical significance: Based on the presented analysis, we highly recommend that further studies use axial T2 mapping due to the higher intra‐ and interreader agreement. Abstract : In this study, T2 maps of 23 symptomatic low back pain patients measured at 3T were assessed in axial and sagittal plane view by two independent observers. The sagittal nucleus pulposus was the best‐performing region‐of‐interest with regard to intra‐ and interobserver agreement in the T2 assessment of the lumbar intervertebral disc. However, the axial NP showed more stable agreements overall and across the value range. In addition, the annular regions showed better inter‐ and intraobserver agreement in the axial plane view.